Serum osmolality, cerebrospinal fluid specific gravity and overt hepatic encephalopathy severity in patients with liver failure. (12th February 2020) - Liotta, Eric M.; Karvellas, Constantine J.; Kim, Minjee; Batra, Ayush; Naidech, Andrew; Prabhakaran, Shyam; Sorond, Farzaneh A.; Kimberly, W. Taylor; Maas, Matthew B.
Abstract: Background and Aims: Hepatic encephalopathy (HE) is a leading contributor to morbidity in liver disease. While hyperammonaemia plays a key role, the mechanisms of cerebral toxicity are unclear. We hypothesized that serum hyperosmolality contributes to HE during acute (ALF) and acute‐on‐chronic liver failure (ACLF) through mechanisms that affect the water and solute composition of the cerebral environment. Methods: We performed a retrospective analysis of serum osmolality, cerebral spinal fluid (CSF) solute density (specific gravity, determined from computed tomography attenuation) and clinical HE severity (Glasgow Coma Score [GCS]) at the time of intensive care admission in a prospectively identified cohort of liver failure patients with overt HE. Results: Seventy‐three patients (39 ALF and 34 ACLF) were included, of whom 28 (38%) were comatose. Serum osmolality (303.9 ± 15.4 mOsm/kg) was elevated despite normal serum sodium (136.6 ± 6.3 mEq/L). Increased osmolality was independently associated with more severe encephalopathy (ordinal adjusted OR 0.26 [95% CI 0.22, 0.31] for higher GCS per standard deviation increase in osmolality) and lower CSF‐specific gravity (linear adjusted β = −0.039 [95% CI −0.069, −0.009] Hounsfield unit per 1 mOsm/kg). Conclusions: In the context of related research, these data suggest that hyperosmolality increases brain exposure to metabolic toxins by blood‐brain barrier alteration and may be a unique therapeutic target.